PELATIHAN PENULISAN ARTIKEL ILMIAH BAGI MAHASISWA FKIP UNIVERSITAS COKROAMINOTO YOGYAKARTA - Anggreini Sarumaha, Yenny (COVIT (Community Service of Tambusai), 2022)
Writing is one of media in communicating to spread knowledge which was got from reaserch results or literature thought. College students are also asked to have writing skills This community service aimed at training college students to have understanding about scientific articles, including parts in articles, procedures in writing article, and steps in publishing article. Moreover, through this community service, college students were expected become more ready and skilled in writing based on their realm and are able to publish their article to any journals, national, or international. The method which were used in this community service were done step by step, started from preparation, implementation, to evaluation. Through this community service was resulted that college tudents showed their ability in determining parts of scientific article and were able to explain the content of each part. They also learnt procedures in writing scientific article. Furthermore, they understood the steps in publishing articles into scientific journals. Even though in the end of the training session there had not been students who finished their article, their progress have already developed into good writing. Keywords: scientific articles, journal, writing training.